Shredding post-fire debris flow likelihood: A field-constrained catchment-scale model of wood-shred surface treatment effectiveness - Molly A. Harrison; Christopher S. Lyell; Felix Smalley; Thomas Keeble; Philip J. Noske; Harry Barton; Rene Van der Sant; Petter Nyman; Patrick N.J. Lane; Gary J. Sheridan (Geomorphology, 2026)

Context matters: emotional responses to urban greening interventions depend on city setting - Freya M. Thomas; Luke Greenacre; Georgia E. Garrard; Richard A. Fuller; Adrian G. Dyer; Ascelin Gordon; Christopher D. Ives; Lee Harrison; Rodney Van der Ree; Sacha Jellinek; Jacinta E. Humphrey; Sarah A. Bekessy (Urban Ecosystems, 2026)
Urban green spaces deliver a remarkable range of human health and well-being benefits, and there is substantial, global effort into incorporating urban greening into the design of cities. However, intense competition for space in cities means small interstitial gaps in the urban fabric are being used for many contemporary green spaces, such as planter boxes or raised garden beds. These small urban greening interventions have become increasingly popular in recent years, especially following the COVID-19 pandemic when access to nature in cities became a key public concern. It is not yet known whether planter boxes in urbanised settings can provide well-being benefits as traditional parks and reserves have been found to. Here we show, using manipulated images, that as much as a 60% difference in a participant’s ( n = 1200) emotional response to a planter box green space is due to changes in city context. This indicates that small green spaces in cities may provide quite different well-being benefits depending on their specific urban setting. As planting context is more important than the focal details of small green space interventions for creating emotional responses in urban residents, city planning could strategically consider not just whether , but where to integrate nature into urban areas to maximise well-being outcomes for residents.

Comparing phosphatised galleried stereom of Ordovician Cincinnaticrinus to modern Endoxocrinus illustrates preservation by micromolding - Benjamin F. Dattilo; Rebecca L. Freeman; David F. Wright; David L. Meyer; James R. Thomka; Samuel Sheray; Michael Harrison; Christopher D. Aucoin (Facies, 2026)
Fossil echinoderm ossicles are often occluded by syntaxial overgrowths which obscure stereom. Phosphatized ossicles from insoluble residues show fine microstructure. We investigated phosphatized stereom in Cincinnaticrinus columnals in insoluble residues from the Ordovician around Cincinnati, Ohio USA. Microstructures appeared to be stereom micromolds. We tested this hypothesis by examining residue and thin sections of undissolved sample using light microscopy, SEM and EDS, resulting in these observations: (1) calcite within phosphatized ossicles is optically aligned and parallel to stem; (2) phosphate deposited centripetally from calcite surfaces, often incompletely filling cavities, leaving a central vug; (3) while calcite is inclusion-free, phosphate contains siliciclastic inclusions from surrounding sediments. These observations suggest that calcite is original, and phosphate was deposited as micromolds. To confirm the phosphatic micromold hypothesis, we compared internodal columnals from the extant isocrinid Endoxocrinus from the Florida Straits using fracture surfaces and epoxy-impregnated thin sections. We then dissolved the thin section calcite, leaving epoxy micromolds for comparison. Schematic 3-D models summarize our reconstructions of structure of the crinoids in both original calcite and micromolds. Through-going solid cylinders are present in Cincinnaticrinus phosphate and Endoxocrinus epoxy molds. In Endoxocrinus , these are molds of stereomic galleries complete with ligaments, confirming Cincinnaticrinus phosphate is also moldic. Galleried stereom of the two crinoids differs in structural details, a divergence that is consistent with phylogenetic evidence of through-going ligaments in an early common ancestor. Preservation by phosphatic micro-molding, interpreted as preserved negative space, facilitates study of stereomic features supporting crinoid soft tissues.

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

The collective application of shorebird tracking data to conservation - Autumn‐Lynn Harrison; Candace Stenzel; Alexandra Anderson; Jessica Howell; Richard B. Lanctot; Marley Aikens; Joaquín Aldabe; Liam A. Berigan; Joël Bêty; Erik Blomberg; Juliana Bosi de Almeida; Andy J. Boyce; et al. (Conservation Biology, 2026)
Addressing urgent conservation issues, such as the drastic declines of North American migratory birds, requires creative, evidence‐based, efficient, and collaborative approaches. The abundance of over 50% of monitored North American shorebird populations has declined by over 50% since 1980. To address these declines, we developed a partnership of scientists and practitioners called the Shorebird Science and Conservation Collective (hereafter the collective ). The collective was founded to translate the combined findings of shorebird tracking data into on‐the‐ground conservation action. With advice from an advisory group, the collective acts as an intermediary whereby dedicated staff collate and analyze data contributions from scientists to support knowledge requests from conservation practitioners. In its first three years, data contributions from 75 organizations include over 7.1 million shorebird observations forming movement paths of 3420 individuals representing 36 species tracked across the Americas and have informed 18 conservation projects spanning education, land and species management, land conservation, and policy requests. Others engaged in translational science from big data could consider similar knowledge‐sharing models that prioritize usable data products, foster collaborative engagement between science experts and practitioners, build focused communities around topics or taxonomic groups, and employ a proof‐of‐concept phase to develop scalable solutions while making progress toward long‐term funding to sustain impact. As the volume of scientific data continues to grow, intermediaries, such as the collective, can be vital liaisons to rapidly integrate and interpret research to support conservation action. Dedicated to the memory of Shiloh Schulte and his conservation achievements for shorebirds.

Digestion behaviour of protein-rich soft foods produced using milk protein, soy protein, and their blends under simulated elderly gastrointestinal tract - Yuxin Qin; Christopher Pillidge; Bernie Harrison; Xiao Dong Chen; Jie Chen; Benu Adhikari (Food Hydrocolloids, 2026)

The Marsupial Database: A comprehensive dataset on the ecology and life history of American and Australasian marsupials - Mariana Silva Ferreira; Rodrigo C. Rossi; Stephane Batista; Kathleen Sena; Kevin R. Bairos‐Novak; Shamia Farhana Shoma; Natália O. Leiner; Diego Astúa; Graeme Coulson; Diana O. Fisher; Natasha D. Harrison; Julian Nicholas Garcia Willmer; et al. (Ecology, 2026)
Marsupials are an important but typically neglected group of mammals that have been overlooked in many comparative analyses of vertebrate ecology and life history evolution. In order to address this knowledge bias, we have developed The Marsupial Database. The Marsupial Database contains traits for a phylogenetically diverse set of 414 extant and recently extinct (last 200 years) species from all seven modern marsupial orders (Dasyuromorphia, Didelphimorphia, Diprotodontia, Microbiotheria, Notoryctemorphia, Paucituberculata, Peramelemorphia) native to 34 countries in the Americas and Australasia. The database comprises 11,054 records of 35 traits describing anatomical, physiological, phenological, and reproductive characteristics, as well as information on species' ecology and current conservation status. Data were collected from 41 sources, comprising published databases and other relevant sources of information. By providing a centralized repository of marsupial ecological and life history traits, The Marsupial Database facilitates analyses of ecological and evolutionary patterns within the group, and also encourages inclusion of marsupials in comparative studies of mammals, vertebrates, and the entire animal kingdom. The Marsupial Database is free from copyright or proprietary restrictions. Please cite this data paper when using the data in publications or scientific presentations.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Development and characterization of protein-rich mixed-protein soft foods for the elderly with swallowing difficulties - Yuxin Qin; Christopher Pillidge; Bernie Harrison; Chenglong Xu; Benu Adhikari (Food Chemistry, 2025)

Proximity to Natural Habitat Is Not Consistently Associated With Pollination Services in Tropical Smallholder Farms: A Systematic Review and Meta‐Analysis - Ennia Bosshard; Mark E. Harrison; Frank van Veen; Chris J. Kettle; Nagaraja Badenahally Chikkarangappa; John E. Banks; Parthiba Basu; Quebin Bosbely Casiá‐Ajché; Bo Dalsgaard; Aditi Dutta; Eunice Enríquez; Natalia Escobedo‐Kenefic; et al. (Ecology Letters, 2025)
Proximity to natural habitat is known to enhance pollination services in large‐scale agriculture, but it remains unclear whether this holds in tropical smallholder farms. These systems are embedded in ecologically complex landscapes, central to global food security, and depend heavily on biodiversity‐derived ecosystem services. We conducted a systematic review and meta‐analysis of 35 studies assessing the relationship between distance to natural habitat and pollinator abundance, species richness, and crop fruit set in tropical smallholder farms. We found no consistent patterns in pollinator abundance and crop fruit set with increasing distance, with relationships highly variable across studies. Similarly variable, yet slightly negative, was the relationship between distance and pollinator species richness. Our findings suggest limited support for the ‘proximity to natural habitat’ hypothesis in tropical smallholder farms, indicating that the inherent complexity of these landscapes may buffer negative effects of distance on pollination. This underscores the importance of maintaining and restoring landscape complexity to sustain biodiversity and ecosystem services such as crop pollination. We also highlight the need for greater methodological consistency and publicly available raw data in future studies to strengthen the evidence base and support management strategies for safeguarding pollination services in tropical smallholder farms.

Mitochondrial dysfunction drives age-related degeneration of the thoracic aorta - Arjune S. Dhanekula; Benjamin R. Harrison; Gavin Pharaoh; Aurora Mattson-Hughes; Stefano Tarantini; Rudolph Stuppard; Scott C. DeRoo; Christopher R. Burke; Billiana Hwang; Jay D. Pal; Michael S. Mulligan; David J. Marcinek (GeroScience, 2025)

Effects of shading aquaculture pools on coral larvae health and production - Christina Langley; Christopher Doropoulos; Dexter dela Cruz; Peter L. Harrison (Aquaculture, 2025)

Environmental and Geographic Conditions on the Breeding Grounds Drive Bergmannian Clines in Nightjars - Aaron A. Skinner; Alicia M. Korpach; Susanne Åkesson; Marja H. Bakermans; Erin M. Bayne; Thomas J. Benson; Giovanni Boano; R. Mark Brigham; Simon S. Christiansen; Greg J. Conway; Christina M. Davy; Ruben Evens; et al. (Journal of Biogeography, 2025)
Aim To evaluate (1) whether three migratory nightjar species (Family Caprimulgidae) adhere to Bergmann's rule, (2) whether environmental factors on the breeding or wintering grounds determine body size, and (3) which mechanistic hypotheses best explain Bergmannian patterns in body size. Location North and South America; Europe and Africa. Taxon Eastern whip‐poor‐will ( Antrostomus vociferus ), Common nighthawk ( Chordeiles minor ) and European nightjar ( Caprimulgus europaeus ). Methods We used GPS tracking and morphometric data to assess competing hypotheses explaining variation in body size for each species, based on their breeding ( n = 3388) and wintering ( n = 189) locations. Results All three species exhibited Bergmannian patterns in body size, providing the first evidence that nightjars conform to Bergmann's rule despite adaptations to severe environmental conditions. Environmental and geographic variables at breeding sites were stronger predictors of body size than wintering‐site variables. Although we found partial support for Bergmann's temperature regulation hypothesis, geographic variables, rather than specific environmental factors, emerged as the strongest predictors of body size variation. Main Conclusions Latitude and longitude correlated strongly with environmental variables and migratory distance; thus, these geographical variables likely encompass many factors that influence body size in nightjars. The present study is among the first to use tracking data from individual birds to understand how environmental pressures across the annual cycle are related to body size. Our findings highlight the critical role of geographic breeding‐ground factors in shaping Bergmannian patterns, offering robust evidence to support nearly two centuries of research since Bergmann's rule was first described in 1847.

Spaceborne LiDAR-derived height-variable forest wind reduction factors (WRF) for improved wildfire spread modelling - Molly A. Harrison; Philip J. Noske; Christopher S. Lyell; Kangmin Moon; Darcy P. Prior; Gary J. Sheridan; Thomas Keeble (Agricultural and Forest Meteorology, 2025)

Seasonal variation of trifluoroacetic acid (TFA) in Antarctic ice cores analysed by direct injection non-suppressed ion chromatography-mass spectrometry (nsIC-MS) - Estrella Sanz Rodriguez; Mingxia Lai; Harrison Stevens; Meredith K. Nation; Christopher T. Plummer; Lenneke M. Jong; Jason L. Roberts; Andrew D. Moy; Andrew R. Bowie; Mark A. Curran; Brett Paull (Science of The Total Environment, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Development and characterization of soy protein-based custard-like soft foods for elderly individuals with swallowing difficulties - Yuxin Qin; Christopher Pillidge; Bernie Harrison; Benu Adhikari (Food Research International, 2025)

Global Marine Flyways Identified for Long‐Distance Migrating Seabirds From Tracking Data - Joanne M. Morten; Ana P. B. Carneiro; Martin Beal; Anne‐Sophie Bonnet‐Lebrun; Maria P. Dias; Marie‐Morgane Rouyer; Autumn‐Lynn Harrison; Jacob González‐Solís; Victoria R. Jones; Virginia A. Garcia Alonso; Michelle Antolos; Javier A. Arata; et al. (Global Ecology and Biogeography, 2025)
Aim To identify the broad‐scale oceanic migration routes (‘marine flyways’) used by multiple pelagic, long‐distance migratory seabirds based on a global compilation of tracking data. Location Global. Time Period 1989–2023. Major Taxa Studied Seabirds (Families: Phaethontidae, Hydrobatidae, Diomedeidae, Procellariidae, Laridae and Stercorariidae). Methods We collated a comprehensive global tracking dataset that included the migratory routes of 48 pelagic and long‐distance migrating seabird species across the Atlantic, Indian, Pacific and Southern Oceans. We grouped individuals that followed similar routes, independent of species or timings of migration, using a dynamic time warping clustering approach. We visualised the routes of each cluster using a line density analysis and used knowledge of seabird spatial ecology to combine the clusters to identify the broad‐scale flyways followed by most pelagic migratory seabirds tracked to‐date at an ocean‐basin scale. Results Six marine flyways were identified across the world's oceans: the Atlantic Ocean Flyway, North Indian Ocean Flyway, East Indian Ocean Flyway, West Pacific Ocean Flyway, Pacific Ocean Flyway and Southern Ocean Flyway. Generally, the flyways were used bidirectionally, and individuals either followed sections of a flyway, a complete flyway, or their movements linked two or more flyways. Transhemispheric figure‐of‐eight routes in the Atlantic and Pacific oceans, and a circumnavigation flyway in the Southern Ocean correspond with major wind ‐ driven ocean currents. Main Conclusions The marine flyways identified demonstrate that pelagic seabirds have similar and repeatable migration routes across ocean‐basin scales. Our study highlights the need to account for connectivity in seabird conservation and provides a framework for international cooperation.

Pathways in formulating foods for the elderly - Yuxin Qin; Christopher Pillidge; Bernie Harrison; Benu Adhikari (Food Research International, 2024)

Comparisons of aerosol generation across different musical instruments and loudness - Jianghan Tian; Henry E. Symons; Natalie A. Watson; Justice Archer; Lauren P. McCarthy; Joshua Harrison; Malcolm Kittle; William J. Browne; Brian Saccente-Kennedy; Ruth Epstein; Christopher M. Orton; James D. Calder; et al. (Journal of Aerosol Science, 2024)

Early Eocene Arctic volcanism from carbonate-metasomatized mantle - James M. D. Day; D. Graham Pearson; Bruce A. Kjarsgaard; Abigail K. Barker; Geoff M. Nowell; Nancy Joyce; David Lowry; Chiranjeeb Sarkar; Christopher Harrison (Contributions to Mineralogy and Petrology, 2023)
Melilitite, nephelinite, basanite, and alkali basalt, along with phonolite differentiates, form the Freemans Cove Complex (FCC) in the south-eastern extremity of Bathurst Island (Nunavut, Canada). New 40 Ar/ 39 Ar chronology indicates their emplacement between ~ 56 and ~ 54 million years ago within a localized extensional structure. Melilitites and nephelinites, along with phonolite differentiates, likely relate to the beginning and end phases of extension, whereas alkali basalts were emplaced during a main extensional episode at ~ 55 Ma. The melilitites, nephelinites, and alkali basalts show no strong evidence for significant assimilation of crust, in contrast to some phonolites. Partial melting occurred within both the garnet- and spinel-facies mantle and sampled sources with He, O, Nd, Hf, and Os isotope characteristics indicative of peridotite with two distinct components. The first, expressed in higher degree partial melts, represents a relatively depleted component (“A”; 3 He/ 4 He ~ 8 R A , ε Nd i ~ + 3 ε Hf i ~ + 7, γ Os i ~ 0). The second was an enriched component (“B” 3 He/ 4 He < 3 R A , ε Nd i < – 1 ε Hf i < + 3, γ Os i > + 70) sampled by the lowest degree partial melts and represents carbonate-metasomatized peridotite. Magmatism in the FCC shows that rifting extended from the Labrador Sea to Bathurst Island and reached a zenith at ~ 55 Ma, during the Eurekan orogeny. The incompatible trace-element abundances and isotopic signatures of FCC rocks indicate melt generation occurred at the base of relatively thin lithosphere at the margin of a thick craton, with no mantle plume influence. FCC melt compositions are distinct from other continental rift magmatic provinces worldwide, and their metasomatized mantle source was plausibly formed synchronously with emplacement of Cretaceous kimberlites. The FCC illustrates that the range of isotopic compositions preserved in continental rift magmas are likely to be dominated by temporal changes in the extent of partial melting, as well as by the timing and degree of metasomatism recorded in the underlying continental lithosphere.

Understanding domestic consumer attitude and behaviour towards energy: A study on the Island of Ireland - Alastair Brown; Harrison Hampton; Aoife Foley; Dylan Furszyfer Del Rio; Christopher Lowans; Brian Caulfield (Energy Policy, 2023)

US regulations to curb alleged cancer causes are ineffectual and compromised by scientific, constitutional and ethical violations - Gio B. Gori; Michael Aschner; Christopher J. Borgert; Samuel M. Cohen; Daniel R. Dietrich; Corrado L. Galli; Helmut Greim; John S. Heslop-Harrison; Sam Kacew; Norbert E. Kaminski; James E. Klaunig; Hans W.J. Marquardt; et al. (Archives of Toxicology, 2023)
The 1958 Delaney amendment to the Federal Food Drug and Cosmetics Act prohibited food additives causing cancer in animals by appropriate tests. Regulators responded by adopting chronic lifetime cancer tests in rodents, soon challenged as inappropriate, for they led to very inconsistent results depending on the subjective choice of animals, test design and conduct, and interpretive assumptions. Presently, decades of discussions and trials have come to conclude it is impossible to translate chronic animal data into verifiable prospects of cancer hazards and risks in humans. Such conclusion poses an existential crisis for official agencies in the US and abroad, which for some 65 years have used animal tests to justify massive regulations of alleged human cancer hazards, with aggregated costs of $trillions and without provable evidence of public health advantages. This article addresses suitable remedies for the US and potentially worldwide, by critically exploring the practices of regulatory agencies vis-á-vis essential criteria for validating scientific evidence. According to this analysis, regulations of alleged cancer hazards and risks have been and continue to be structured around arbitrary default assumptions at odds with basic scientific and legal tests of reliable evidence. Such practices raise a manifold ethical predicament for being incompatible with basic premises of the US Constitution, and with the ensuing public expectations of testable truth and transparency from government agencies. Potential remedies in the US include amendments to the US Administrative Procedures Act, preferably requiring agencies to justify regulations compliant with the Daubert opinion of the Daubert ruling of the US Supreme Court, which codifies the criteria defining reliable scientific evidence . International reverberations are bound to follow what remedial actions may be taken in the US, the origin of current world regulatory procedures to control alleged cancer causing agents.

Macroalgae exhibit diverse responses to human disturbances on coral reefs - Sara E. Cannon; Simon D. Donner; Angela Liu; Pedro C. González Espinosa; Andrew H. Baird; Julia K. Baum; Andrew G. Bauman; Maria Beger; Cassandra E. Benkwitt; Matthew J. Birt; Yannick Chancerelle; Joshua E. Cinner; et al. (Global Change Biology, 2023)
Scientists and managers rely on indicator taxa such as coral and macroalgal cover to evaluate the effects of human disturbance on coral reefs, often assuming a universally positive relationship between local human disturbance and macroalgae. Despite evidence that macroalgae respond to local stressors in diverse ways, there have been few efforts to evaluate relationships between specific macroalgae taxa and local human‐driven disturbance. Using genus‐level monitoring data from 1205 sites in the Indian and Pacific Oceans, we assess whether macroalgae percent cover correlates with local human disturbance while accounting for factors that could obscure or confound relationships. Assessing macroalgae at genus level revealed that no genera were positively correlated with all human disturbance metrics. Instead, we found relationships between the division or genera of algae and specific human disturbances that were not detectable when pooling taxa into a single functional category, which is common to many analyses. The convention to use percent cover of macroalgae as an indication of local human disturbance therefore likely obscures signatures of local anthropogenic threats to reefs. Our limited understanding of relationships between human disturbance, macroalgae taxa, and their responses to human disturbances impedes the ability to diagnose and respond appropriately to these threats.

Middle Pleistocene Pongo from Ganxian Cave in southern China with implications for understanding dental size evolution in orangutans - Hua Liang; Terry Harrison; Qingfeng Shao; Jean-Jacques Bahain; Jianxin Zhao; Christopher J. Bae; Wei Liao; Wei Wang (Journal of Human Evolution, 2023)

Residual correlation and ensemble modelling to improve crop and grassland models - Renáta Sándor; Fiona Ehrhardt; Peter Grace; Sylvie Recous; Pete Smith; Val Snow; Jean-François Soussana; Bruno Basso; Arti Bhatia; Lorenzo Brilli; Jordi Doltra; Christopher D. Dorich; et al. (Environmental Modelling & Software, 2023)

Quantifying spatial extents of artificial versus natural reefs in the seascape - D’amy N. Steward; Avery B. Paxton; Nathan M. Bacheler; Christina M. Schobernd; Keith Mille; Jeffrey Renchen; Zach Harrison; Jordan Byrum; Robert Martore; Cameron Brinton; Kenneth L. Riley; J. Christopher Taylor; et al. (Frontiers in Marine Science, 2022)
With increasing human uses of the ocean, existing seascapes containing natural habitats, such as biogenic reefs or plant-dominated systems, are supplemented by novel, human-made habitats ranging from artificial reefs to energy extraction infrastructure and shoreline installments. Despite the mixture of natural and artificial habitats across seascapes, the distribution and extent of these two types of structured habitats are not well understood but are necessary pieces of information for ocean planning and resource management decisions. Through a case study, we quantified the amount of seafloor in the southeastern US (SEUS; 103,220 km 2 in the Atlantic Ocean; 10 – 200 m depth) covered by artificial reefs and natural reefs. We developed multiple data-driven approaches to quantify the extent of artificial reefs within state-managed artificial reef programs, and then drew from seafloor maps and published geological and predictive seafloor habitat models to develop three estimates of natural reef extent. Comparisons of the extent of natural and artificial reefs revealed that artificial reefs account for substantially less habitat (average of two estimates 3 km 2 ; <0.01% of SEUS) in the region than natural reefs (average of three estimates 2,654 km 2 ; 2.57% of SEUS) and that this pattern holds across finer regional groupings (e.g., states, depth bins). Our overall estimates suggest that artificial reef coverage is several orders of magnitude less than natural reef coverage. While expansive seafloor mapping and characterization efforts are still needed in SEUS waters, our results fill information gaps regarding the extent of artificial and natural reef habitats in the region, providing support for ecosystem-based management, and demonstrating an approach applicable to other regions.

First isolation of Flavobacterium psychrophilum from wild adult Great Lakes lake whitefish ( Coregonus clupeaformis ) - Courtney E. Harrison; Christopher K. Knupp; Travis O. Brenden; Mark P. Ebener; Thomas P. Loch (Journal of Fish Diseases, 2022)
Lake whitefish ( Coregonus clupeaformis ; LWF) is an economically and ecologically valuable native species to the Great Lakes, but recent declines in their recruitment have generated significant concern about their future viability. Although studies have sought to identify factors contributing to declining recruitment, the potential role(s) of infectious diseases has not been thoroughly investigated. In 2018 and 2019, adult LWF were collected from Lakes Superior, Michigan, and Huron for clinical examination and bacteriological analyses. Herein, we describe the first isolation of Flavobacterium psychrophilum , aetiological agent of bacterial coldwater disease (BCWD) and rainbow trout fry syndrome (RTFS), from systemically infected adult LWF. Bacterial isolates were yellow‐orange, Gram‐negative, filamentous bacilli that were oxidase and catalase positive, and produced a flexirubin‐type pigment in 3% potassium hydroxide. Isolate identity was confirmed via F. psychrophilum ‐specific PCR, and multilocus sequence typing revealed three new singleton sequence types (STs) that were distinct from all previously described F. psychrophilum STs. The prevalence of F. psychrophilum infections was 3.3, 1.7, and 0.0% in Lakes Superior, Michigan and Huron respectively. Findings illustrate the potential for F. psychrophilum to cause systemic infections in adult LWF and highlight the need for future studies to investigate the bacterium's potential role in declining LWF recruitment.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Development of duplex qPCR targeting Carnobacterium maltaromaticum and Vagococcus salmoninarum - Isaac Standish; Rebekah McCann; Corey Puzach; Eric Leis; Jennifer Bailey; Sara Dziki; Ryan Katona; Ellen Lark; Carey Edwards; Brandon Keesler; Stephen Reichley; Stacy King; et al. (Journal of Fish Diseases, 2022)
In November 2018, Vagococcus salmoninarum was identified as the causative agent of a chronic coldwater streptococcosis epizootic in broodstock brook trout ( Salvelinus fontinalis ) at the Iron River National Fish Hatchery in Wisconsin, USA. By February 2019, the epizootic spread to adjacent raceways containing broodstock lake trout ( Salvelinus namaycush ), whereby fish were found to be coinfected with Carnobacterium maltaromaticum and V . salmoninarum . To differentiate these two pathogens and determine the primary cause of the lake trout morbidity, a quantitative real‐time PCR (qPCR) was developed targeting the C . maltaromaticum phenylalanyl‐tRNA synthase alpha subunit ( pheS ) gene. The qPCR was combined with a V . salmoninarum qPCR, creating a duplex qPCR assay that simultaneously quantitates C. maltaromaticum and V . salmoninarum concentrations in individual lake trout tissues, and screens presumptive isolates from hatchery inspections and wild fish from national fish hatchery source waters throughout the Great Lakes basin. Vagococcus salmoninarum and C. maltaromaticum were co‐detected in broodstock brook trout from two tribal hatcheries and C. maltaromaticum was present in wild fish in source waters of several national fish hatcheries. This study provides a powerful new tool to differentiate and diagnose two emerging Gram‐positive bacterial pathogens.

The EU chemicals strategy for sustainability: in support of the BfR position - Frank A. Barile; Sir Colin Berry; Bas Blaauboer; Alan Boobis; Herrmann M. Bolt; Christopher Borgert; Wolfgang Dekant; Daniel Dietrich; Jose L. Domingo; Corrado L. Galli; Gio Batta Gori; Helmut Greim; et al. (Archives of Toxicology, 2021)
The EU chemicals strategy for sustainability (CSS) asserts that both human health and the environment are presently threatened and that further regulation is necessary. In a recent Guest Editorial, members of the German competent authority for risk assessment, the BfR, raised concerns about the scientific justification for this strategy. The complexity and interdependence of the networks of regulation of chemical substances have ensured that public health and wellbeing in the EU have continuously improved. A continuous process of improvement in consumer protection is clearly desirable but any initiative directed towards this objective must be based on scientific knowledge. It must not confound risk with other factors in determining policy. This conclusion is fully supported in the present Commentary including the request to improve both, data collection and the time-consuming and bureaucratic procedures that delay the publication of regulations.

Ensemble modelling, uncertainty and robust predictions of organic carbon in long‐term bare‐fallow soils - Roberta Farina; Renata Sándor; Mohamed Abdalla; Jorge Álvaro‐Fuentes; Luca Bechini; Martin A. Bolinder; Lorenzo Brilli; Claire Chenu; Hugues Clivot; Massimiliano De Antoni Migliorati; Claudia Di Bene; Christopher D. Dorich; et al. (Global Change Biology, 2021)
Simulation models represent soil organic carbon (SOC) dynamics in global carbon (C) cycle scenarios to support climate‐change studies. It is imperative to increase confidence in long‐term predictions of SOC dynamics by reducing the uncertainty in model estimates. We evaluated SOC simulated from an ensemble of 26 process‐based C models by comparing simulations to experimental data from seven long‐term bare‐fallow (vegetation‐free) plots at six sites: Denmark (two sites), France, Russia, Sweden and the United Kingdom. The decay of SOC in these plots has been monitored for decades since the last inputs of plant material, providing the opportunity to test decomposition without the continuous input of new organic material. The models were run independently over multi‐year simulation periods (from 28 to 80 years) in a blind test with no calibration (Bln) and with the following three calibration scenarios, each providing different levels of information and/or allowing different levels of model fitting: (a) calibrating decomposition parameters separately at each experimental site (Spe); (b) using a generic, knowledge‐based, parameterization applicable in the Central European region (Gen); and (c) using a combination of both (a) and (b) strategies (Mix). We addressed uncertainties from different modelling approaches with or without spin‐up initialization of SOC. Changes in the multi‐model median (MMM) of SOC were used as descriptors of the ensemble performance. On average across sites, Gen proved adequate in describing changes in SOC, with MMM equal to average SOC (and standard deviation) of 39.2 (±15.5) Mg C/ha compared to the observed mean of 36.0 (±19.7) Mg C/ha (last observed year), indicating sufficiently reliable SOC estimates. Moving to Mix (37.5 ± 16.7 Mg C/ha) and Spe (36.8 ± 19.8 Mg C/ha) provided only marginal gains in accuracy, but modellers would need to apply more knowledge and a greater calibration effort than in Gen, thereby limiting the wider applicability of models.

Sleeping trees and sleep-related behaviours of the siamang (Symphalangus syndactylus) in a tropical lowland rainforest, Sumatra, Indonesia - Nathan J. Harrison; Ross A. Hill; Cici Alexander; Christopher D. Marsh; Matthew G. Nowak; Abdullah Abdullah; Helen D. Slater; Amanda H. Korstjens (Primates, 2021)
Sleeping tree selection and related behaviours of a family group and a solitary female siamang ( Symphalangus syndactylus ) were investigated over a 5-month period in northern Sumatra, Indonesia. We performed all day follows, sleeping tree surveys and forest plot enumerations in the field. We tested whether: (1) physical characteristics of sleeping trees and the surrounding trees, together with siamang behaviours, supported selection based on predation risk and access requirements; (2) the preferences of a solitary siamang were similar to those of a family group; and (3) sleeping site locations within home ranges were indicative of home range defence, scramble competition with other groups or other species, or food requirements. Our data showed that (1) sleeping trees were tall, emergent trees with some, albeit low, connectivity to the neighbouring canopy, and that they were surrounded by other tall trees. Siamangs showed early entry into and departure from sleeping trees, and slept at the ends of branches. These results indicate that the siamangs’ choice of sleeping trees and related behaviours were strongly driven by predator avoidance. The observed regular reuse of sleeping sites, however, did not support anti-predation theory. (2) The solitary female displayed selection criteria for sleeping trees that were similar to those of the family group, but she slept more frequently in smaller trees than the latter. (3) Siamangs selected sleeping trees to avoid neighbouring groups, monopolise resources (competition), and to be near their last feeding tree. Our findings indicate selectivity in the siamangs’ use of sleeping trees, with only a few trees in the study site being used for this purpose. Any reduction in the availability of such trees might make otherwise suitable habitat unsuitable for these highly arboreal small apes.

Hyperphosphorylation Renders Tau Prone to Aggregate and to Cause Cell Death - Mengyu Liu; Dexin Sui; Thomas Dexheimer; Stacy Hovde; Xiexiong Deng; Kuang-Wei Wang; Hsin Lian Lin; Hsiao-Tien Chien; Hye Kyong Kweon; Nora Sheen Kuo; Christopher A. Ayoub; Daniela Jimenez-Harrison; et al. (Molecular Neurobiology, 2020)

Multispecific coral spawning events and extended breeding periods on an equatorial reef - Marine Gouezo; Christopher Doropoulos; Katharina Fabricius; Dawnette Olsudong; Victor Nestor; Haruko Kurihara; Yimnang Golbuu; Peter Harrison (Coral Reefs, 2020)

Effects of body size on estimation of mammalian area requirements - Michael J. Noonan; Christen H. Fleming; Marlee A. Tucker; Roland Kays; Autumn‐Lynn Harrison; Margaret C. Crofoot; Briana Abrahms; Susan C. Alberts; Abdullahi H. Ali; Jeanne Altmann; Pamela Castro Antunes; Nina Attias; et al. (Conservation Biology, 2020)
Accurately quantifying species’ area requirements is a prerequisite for effective area‐based conservation. This typically involves collecting tracking data on species of interest and then conducting home‐range analyses. Problematically, autocorrelation in tracking data can result in space needs being severely underestimated. Based on the previous work, we hypothesized the magnitude of underestimation varies with body mass, a relationship that could have serious conservation implications. To evaluate this hypothesis for terrestrial mammals, we estimated home‐range areas with global positioning system (GPS) locations from 757 individuals across 61 globally distributed mammalian species with body masses ranging from 0.4 to 4000 kg. We then applied block cross‐validation to quantify bias in empirical home‐range estimates. Area requirements of mammals 1, meaning the scaling of the relationship changed substantially at the upper end of the mass spectrum.

Human exposure to synthetic endocrine disrupting chemicals (S-EDCs) is generally negligible as compared to natural compounds with higher or comparable endocrine activity: how to evaluate the risk of the S-EDCs? - Herman Autrup; Frank A. Barile; Sir Colin Berry; Bas J. Blaauboer; Alan Boobis; Herrmann Bolt; Christopher J. Borgert; Wolfgang Dekant; Daniel Dietrich; Jose L. Domingo; Gio Batta Gori; Helmut Greim; et al. (Archives of Toxicology, 2020)
Theoretically, both synthetic endocrine disrupting chemicals (S-EDCs) and natural (exogenous and endogenous) endocrine disrupting chemicals (N-EDCs) can interact with endocrine receptors and disturb hormonal balance. However, compared to endogenous hormones, S-EDCs are only weak partial agonists with receptor affinities several orders of magnitude lower. Thus, to elicit observable effects, S-EDCs require considerably higher concentrations to attain sufficient receptor occupancy or to displace natural hormones and other endogenous ligands. Significant exposures to exogenous N-EDCs may result from ingestion of foods such as soy-based diets, green tea and sweet mustard. While their potencies are lower as compared to natural endogenous hormones, they usually are considerably more potent than S-EDCs. Effects of exogenous N-EDCs on the endocrine system were observed at high dietary intakes. A causal relation between their mechanism of action and these effects is established and biologically plausible. In contrast, the assumption that the much lower human exposures to S-EDCs may induce observable endocrine effects is not plausible. Hence, it is not surprising that epidemiological studies searching for an association between S-EDC exposure and health effects have failed. Regarding testing for potential endocrine effects, a scientifically justified screen should use in vitro tests to compare potencies of S-EDCs with those of reference N-EDCs. When the potency of the S-EDC is similar or smaller than that of the N-EDC, further testing in laboratory animals and regulatory consequences are not warranted.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Carbohydrate hydrogel beverage provides no additional cycling performance benefit versus carbohydrate alone - Daniel A. Baur; Harrison R. Toney; Michael J. Saunders; Katherine G. Baur; Nicholas D. Luden; Christopher J. Womack (European Journal of Applied Physiology, 2019)

Identification of flavonoids as regulators of YbeY activity in Liberibacter asiaticus - Ran Zuo; Aline de Oliveira; Enrica Bullita; Maria Ines Torino; Kaylie A. Padgett‐Pagliai; Christopher L. Gardner; Natalie A. Harrison; Danilo da Silva; Marcelo L. Merli; Claudio F. Gonzalez; Graciela L. Lorca (Environmental Microbiology, 2019)
Summary Liberibacter asiaticus is the prevalent causative pathogen of Huanglongbing or citrus greening disease, which has resulted in a devastating crisis in the citrus industry. A thorough understanding of this pathogen's physiology and mechanisms to control cell survival is critical in the identification of therapeutic targets. YbeY is a highly conserved bacterial RNase that has been implicated in multiple roles. In this study, we evaluated the biochemical characteristics of the L . asiaticus YbeY (CLIBASIA_01560) and assessed its potential as a target for antimicrobials. YbeY Las was characterized as an endoribonuclease with activity on 3′ and 5′ termini of 16S and 23S rRNAs, and the capacity to suppress the E . coli ΔybeY phenotype. We predicted the YbeY Las protein:ligand interface and subsequently identified a flavone compound, luteolin, as a selective inhibitor. Site‐directed mutagenesis was subsequently used to identify key residues involved in the catalytic activity of YbeY Las . Further evaluation of naturally occurring flavonoids in citrus trees indicated that both flavones and flavonols had potent inhibitory effects on YbeY Las . Luteolin was subsequently examined for efficacy against L . asiaticus in Huanglongbing‐infected citrus trees, where a significant reduction in L . asiaticus gene expression was observed.

Correction to: Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Effects of an Experimental Water-level Drawdown on Methane Emissions from a Eutrophic Reservoir - Jake J. Beaulieu; David A. Balz; M. Keith Birchfield; John A. Harrison; Christopher T. Nietch; Michelle C. Platz; William C. Squier; Sarah Waldo; John T. Walker; Karen M. White; Jade L. Young (Ecosystems, 2018)

Assessing uncertainties in crop and pasture ensemble model simulations of productivity and N 2 O emissions - Fiona Ehrhardt; Jean‐François Soussana; Gianni Bellocchi; Peter Grace; Russel McAuliffe; Sylvie Recous; Renáta Sándor; Pete Smith; Val Snow; Massimiliano de Antoni Migliorati; Bruno Basso; Arti Bhatia; et al. (Global Change Biology, 2018)
Simulation models are extensively used to predict agricultural productivity and greenhouse gas emissions. However, the uncertainties of (reduced) model ensemble simulations have not been assessed systematically for variables affecting food security and climate change mitigation, within multi‐species agricultural contexts. We report an international model comparison and benchmarking exercise, showing the potential of multi‐model ensembles to predict productivity and nitrous oxide (N 2 O) emissions for wheat, maize, rice and temperate grasslands. Using a multi‐stage modelling protocol, from blind simulations (stage 1) to partial (stages 2–4) and full calibration (stage 5), 24 process‐based biogeochemical models were assessed individually or as an ensemble against long‐term experimental data from four temperate grassland and five arable crop rotation sites spanning four continents. Comparisons were performed by reference to the experimental uncertainties of observed yields and N 2 O emissions. Results showed that across sites and crop/grassland types, 23%–40% of the uncalibrated individual models were within two standard deviations ( SD ) of observed yields, while 42 (rice) to 96% (grasslands) of the models were within 1 SD of observed N 2 O emissions. At stage 1, ensembles formed by the three lowest prediction model errors predicted both yields and N 2 O emissions within experimental uncertainties for 44% and 33% of the crop and grassland growth cycles, respectively. Partial model calibration (stages 2–4) markedly reduced prediction errors of the full model ensemble E‐median for crop grain yields (from 36% at stage 1 down to 4% on average) and grassland productivity (from 44% to 27%) and to a lesser and more variable extent for N 2 O emissions. Yield‐scaled N 2 O emissions (N 2 O emissions divided by crop yields) were ranked accurately by three‐model ensembles across crop species and field sites. The potential of using process‐based model ensembles to predict jointly productivity and N 2 O emissions at field scale is discussed.

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

QTL and major genes influencing grain yield potential in soft red winter wheat adapted to the southern United States - Christopher K. Addison; R. Esten Mason; Gina Brown-Guedira; Mohammed Guedira; Yuanfeng Hao; Randall G. Miller; Nithya Subramanian; Dennis N. Lozada; Andrea Acuna; Maria N. Arguello; Jerry W. Johnson; Amir M. H. Ibrahim; et al. (Euphytica, 2016)

A genome-wide association study for colorectal cancer identifies a risk locus in 14q23.1 - Mathieu Lemire; Conghui Qu; Lenora W. M. Loo; Syed H. E. Zaidi; Hansong Wang; Sonja I. Berndt; Stéphane Bézieau; Hermann Brenner; Peter T. Campbell; Andrew T. Chan; Jenny Chang-Claude; Mengmeng Du; et al. (Human Genetics, 2015)

Skeletal muscle satellite cell migration to injured tissue measured with111In-oxine and high-resolution SPECT imaging - Jennifer L. Elster; Christopher R. Rathbone; Zhonglin Liu; Xiasong Liu; Harrison H. Barrett; Robert P. Rhoads; Ronald E. Allen (Journal of Muscle Research and Cell Motility, 2013)

The L egionella pneumophila orphan sensor kinase LqsT regulates competence and pathogen–host interactions as a component of the LAI ‐1 circuit - Aline Kessler; Ursula Schell; Tobias Sahr; André Tiaden; Christopher Harrison; Carmen Buchrieser; Hubert Hilbi (Environmental Microbiology, 2013)
Summary L egionella pneumophila is an amoeba‐resistant opportunistic pathogen that performs cell–cell communication through the signalling molecule 3‐hydroxypentadecane‐4‐one ( LAI ‐1, L egionella autoinducer‐1). The lqs ( L egionella quorum sensing) gene cluster encodes the LAI ‐1 autoinducer synthase LqsA , the cognate sensor kinase LqsS and the response regulator LqsR . Here we show that the Lqs system includes an ‘orphan’ homologue of LqsS termed LqsT . Compared with wild‐type L . pneumophila , strains lacking lqsT or both lqsS and lqsT show increased salt resistance, greatly enhanced natural competence for DNA acquisition and impaired uptake by phagocytes. Sensitive novel single round growth assays and competition experiments using A canthamoeba castellanii revealed that Δ lqsT and Δ lqsS ‐Δ lqsT , as well as Δ lqsA and other lqs mutant strains are impaired for intracellular growth and cannot compete against wild‐type bacteria upon co‐infection. In contrast to the Δ lqsS strain, Δ lqsT does not produce extracellular filaments. The phenotypes of the Δ lqsS ‐Δ lqsT strain are partially complemented by either lqsT or lqsS , but are not reversed by overexpression of lqsA , suggesting that LqsT and LqsS are the sole LAI ‐1‐responsive sensor kinases in L . pneumophila . In agreement with the different phenotypes of the Δ lqsT and Δ lqsS strains, lqsT and lqsS are differentially expressed in the post‐exponential growth phase, and transcriptome studies indicated that 90% of the genes, which are downregulated in absence of lqsT , are upregulated in absence of lqsS . Reciprocally regulated genes encode components of a 133 kb genomic ‘fitness island’ or translocated effector proteins implicated in virulence. Together, these results reveal a unique organization of the L . pneumophila Lqs system comprising two partially antagonistic LAI ‐1‐responsive sensor kinases, LqsT and LqsS , which regulate distinct pools of genes implicated in pathogen–host cell interactions, competence, expression of a genomic island or production of extracellular filaments.

Genomic Resources for Evolutionary Studies in the Large, Diverse, Tropical Genus, Begonia - Adrian Christopher Brennan; Stephen Bridgett; Mobina Shaukat Ali; Nicola Harrison; Andrew Matthews; Jaume Pellicer; Alex David Twyford; Catherine Anne Kidner (Tropical Plant Biology, 2012)

Population stratification may bias analysis of PGC-1α as a modifier of age at Huntington disease motor onset - Eliana Marisa Ramos; Jeanne C. Latourelle; Ji-Hyun Lee; Tammy Gillis; Jayalakshmi S. Mysore; Ferdinando Squitieri; Alba Di Pardo; Stefano Di Donato; Michael R. Hayden; Patrick J. Morrison; Martha Nance; Christopher A. Ross; et al. (Human Genetics, 2012)

Pacific Rim Forestry / Silviculture and Forest Ecology - Vishal Singh Negi; Archana Pal; Ratnesh Singh; Dulal Borthakur; Archana Pala; Vishal Singh Negi; Dulal Borthakur; Isabel Rushanaedy; Tyler Jones; Nicklos Dudley; Dulal Borthakur; Jannai Yafuso; et al. (Journal of Forestry, 2011)
Leucaena leucocephala (leucaena) is an important agroforestry tree of tropics and subtropics due to its protein rich foliages, ability to grow on poor soils, and high level of tolerance to various stresses including drought and diseases. We hypothesized that leucaena have a unique set of genes which confer tolerance to various abiotic and biotic stresses and these genes are either absent or not expressed in other legumes that are susceptible to these stress conditions. Interspecies suppression subtractive hybridization (iSSH) was performed to identify some unique genes from leucaena using cDNAs from leucaena and Acacia confusa (acacia) as the tester and driver, respectively. We identified 100 leucaena genes showing homology to various plant genes with known functions, of which 23 genes had homology to various stress-related proteins including chitinase, PR-10 protein, wound-stress protein, type-2 metallothionein, thaumatin-like protein, disease resistance response protein, cysteine proteinase, and kunitz trypsin inhibitor. We also identified 50 leucaena genes which either had homology to hypothetical proteins (HyPs) or had no homology at all. Putative functions of 15 HyPs were predicted using conserved domain and PSI-BLAST analyses. Linear motif analyses identified 17 HyPs with MAPK recognition motif, which is involved in signaling pathways, including stress responses. This study identified 23 known and some putative unique stress-related genes from leucaena which may serve as a useful source of stress-tolerance genes for tree and crop improvement in the future.

Invasion in a heterogeneous world: resistance, coexistence or hostile takeover? - Brett A. Melbourne; Howard V. Cornell; Kendi F. Davies; Christopher J. Dugaw; Sarah Elmendorf; Amy L. Freestone; Richard J Hall; Susan Harrison; Alan Hastings; Matt Holland; Marcel Holyoak; John Lambrinos; et al. (Ecology Letters, 2007)
We review and synthesize recent developments in the study of the invasion of communities in heterogeneous environments, considering both the invasibility of the community and impacts to the community. We consider both empirical and theoretical studies. For each of three major kinds of environmental heterogeneity (temporal, spatial and invader‐driven), we find evidence that heterogeneity is critical to the invasibility of the community, the rate of spread, and the impacts on the community following invasion. We propose an environmental heterogeneity hypothesis of invasions, whereby heterogeneity both increases invasion success and reduces the impact to native species in the community, because it promotes invasion and coexistence mechanisms that are not possible in homogeneous environments. This hypothesis could help to explain recent findings that diversity is often increased as a result of biological invasions. It could also explain the scale dependence of the diversity–invasibility relationship. Despite the undoubted importance of heterogeneity to the invasion of communities, it has been studied remarkably little and new research is needed that simultaneously considers invasion, environmental heterogeneity and community characteristics. As a young field, there is an unrivalled opportunity for theoreticians and experimenters to work together to build a tractable theory informed by data.

Climate factors influencing bacterial count in background air samples - Roy M. Harrison; Alan M. Jones; Peter D. E. Biggins; Nigel Pomeroy; Christopher S. Cox; Stephen P. Kidd; Jon L. Hobman; Nigel L. Brown; Alan Beswick (International Journal of Biometeorology, 2005)

The spatial spread of invasions: new developments in theory and evidence - Alan Hastings; Kim Cuddington; Kendi F. Davies; Christopher J. Dugaw; Sarah Elmendorf; Amy Freestone; Susan Harrison; Matthew Holland; John Lambrinos; Urmila Malvadkar; Brett A. Melbourne; Kara Moore; et al. (Ecology Letters, 2005)
We review and synthesize recent developments in the study of the spread of invasive species, emphasizing both empirical and theoretical approaches. Recent theoretical work has shown that invasive species spread is a much more complex process than the classical models suggested, as long range dispersal events can have a large influence on the rate of range expansion through time. Empirical work goes even further, emphasizing the role of spatial heterogeneity, temporal variability, other species, and evolution. As in some of the classic work on spread, the study of range expansion of invasive species provides unique opportunities to use differences between theory and data to determine the important underlying processes that control spread rates.

Effects of halothane, isoflurane, sevoflurane and desflurane on contraction of ventricular myocytes from streptozotocin-induced diabetic rats - Mark Graham; Anwar Qureshi; Rabiah Noueihed; Simon Harrison; Frank Christopher Howarth (Molecular and Cellular Biochemistry, 2004)

Genetic mapping of an insertional hydrocephalus-inducing mutation allelic to hy3 - Michael L. Robinson; Carl E. Allen; Brian E. Davy; William J. Durfee; Frederick F. Elder; Christopher S. Elliott; Wilbur R. Harrison (Mammalian Genome, 2002)

Copper chaperones: function, structure and copper-binding properties - Mark D. Harrison; Christopher E. Jones; C. T. Dameron (JBIC Journal of Biological Inorganic Chemistry, 1999)

Perceptions of Species Abundance, Distribution, and Diversity: Lessons from Four Decades of Sampling on a Government-Managed Reserve - J. Whitfield Gibbons; Vincent J. Burke; Jeffrey E. Lovich; Raymond D. Semlitsch; Tracey D. Tuberville; J. Russell Bodie; Judith L. Greene; Peter H. Niewiarowski; Howard H. Whiteman; David E. Scott; Joseph H. K. Pechmann; Christopher R. Harrison; et al. (Environmental Management, 1997)